Analysis of difficulties in solving high-level thinking ability questions for middle school students - Setiawan, Setiawan; Anwar, Nur; Julrissani, Julrissani (International Journal of Trends in Mathematics Education Research, 2023)
This study aims to determine students' higher order thinking skills (HOTS) and to analyze the difficulties experienced by students in solving HOTS questions at SMP Negeri 10 Lhokseumawe. The study used was descriptive qualitative research which was carried out by class VIII students of SMP Negeri 10 Lhokseumawe. The collection of data used is a test in the form of descriptions with material forms and algebraic operations and interviews. The data analysis technique used follows the Miles and Huberman model with data reduction, data presentation and drawing conclusions. The results showed that the students' high-level thinking skills were still in the low category. This can be seen from the success of each aspect of students' higher order thinking skills, namely the ability to analyze by 70.83%, the ability to evaluate by 12.50% and the ability to create or be creative by 33.33%. The results of the interviews found that students were not familiar with questions in the form of application of concepts or problem-solving, and there were still many students who did not have reinforcement of material concept abilities.